2019
DOI: 10.3389/fimmu.2019.01588
|View full text |Cite
|
Sign up to set email alerts
|

Inactivated Lactobacillus plantarum Carrying a Surface-Displayed Ag85B-ESAT-6 Fusion Antigen as a Booster Vaccine Against Mycobacterium tuberculosis Infection

Abstract: Vaccination is considered the most effective strategy for controlling tuberculosis (TB). The existing vaccine, the Bacille Calmette-Guérin (BCG), although partially protective, has a number of limitations. Therefore, there is a need for developing new TB vaccines and several strategies are currently exploited including the use of viral and bacterial delivery vectors. We have previously shown that Lactobacillus plantarum ( Lp ) producing Ag85B and ESAT-6 antigens fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 72 publications
1
14
0
Order By: Relevance
“…Because lactobacilli are safe and may have immune-stimulating adjuvant effects [3][4][5][6][7][8] , they are promising delivery vectors for antigens and other medical molecules. Studies with animal models have repeatedly demonstrated the potential of antigen producing lactobacilli to induce specific immune responses [9][10][11][12][13][14][15][16] and one such Lactobacillus has even reached clinical tests 17 . Ideally, the antigens should be sufficiently protected from proteolytic digestion and other damage in the harsh environment of the gastro-intestinal tract, while at the same time being sufficiently exposed to provoke favorable immune responses at mucosal surfaces.…”
mentioning
confidence: 99%
“…Because lactobacilli are safe and may have immune-stimulating adjuvant effects [3][4][5][6][7][8] , they are promising delivery vectors for antigens and other medical molecules. Studies with animal models have repeatedly demonstrated the potential of antigen producing lactobacilli to induce specific immune responses [9][10][11][12][13][14][15][16] and one such Lactobacillus has even reached clinical tests 17 . Ideally, the antigens should be sufficiently protected from proteolytic digestion and other damage in the harsh environment of the gastro-intestinal tract, while at the same time being sufficiently exposed to provoke favorable immune responses at mucosal surfaces.…”
mentioning
confidence: 99%
“…Lactic acid bacteria, non-sporulating Gram-positive bacteria, have also been widely used as vaccine vectors due to their known safety and well-established genetic toolkit [106]. Specifically, inactivated Lactobacillus plantarum was recently investigated as a booster to BCG due to its immunomodulatory effects and adjuvant properties.…”
Section: Bacterial Vector Vaccinesmentioning
confidence: 99%
“…Specifically, inactivated Lactobacillus plantarum was recently investigated as a booster to BCG due to its immunomodulatory effects and adjuvant properties. L. plantarum expressing Ag85B-ESAT-6 fused to a DC targeting peptide on the bacterial surface was the first inactivated L. plantarum vectored vaccine to show increased protection in the lungs against M. tb H37Rv when used as an intranasal boost to BCG (p < 0.05) compared to BCG alone [106]. This observed protection may be due, in part, to high levels of IFNγ, high frequency of polyfunctional T cells, and production of lung IgA [106].…”
Section: Bacterial Vector Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations